Structure in the radio counterpart to the 2004 December 27 giant flare from SGR 1806-20 - Fender, R.; Muxlow, T.; Garrett, M.; Kouveliotou, C.; Gaensler, B.; Garrington, S.; Paragi, Z.; Tudose, V.; Miller-Jones, James; Spencer, R.; Wijers, R.; Taylor, G. (Wiley-Blackwell Publishing Ltd., 2006)
On 2004 December 27, the magnetar SGR 1806-20 underwent an enormous outburst resulting in the formation of an expanding, moving, and fading radio source. We report observations of this radio source with the Multi-Element Radio-Linked Interferometer Network and the Very Long Baseline Array. The observations confirm the elongation and expansion already reported based on observations at lower angular resolutions, but suggest that at early epochs the structure is not consistent with the very simplest models such as a smooth flux distribution. In particular, there appears to be significant structure on small angular scales, with ~10 per cent of the radio flux arising on angular scales <=100 milliarcsec. This structure may correspond to localized sites of particle acceleration during the early phases of expansion and interaction with the ambient medium.